Phenotypic characterization of Garcinia species:Implications for conservation and breeding - Tripathi, Prakash Chandra; Kanupriya, C; Singh, Pritee; Radhika, V (Journal of Horticultural Sciences, 2024)
The genus Garcinia (Clusiaceae) is renowned for its medicinal and nutritional value, yet its phenotypic diversity remains underexplored. In this study, 54 accessions from four species viz., G. indica (29), G. xanthochymus (13), G. gummi-gutta (10), and G. mundro (2), were evaluated for morphological and pomological traits. Significant variability was observed for various morphological traits. Leaf length ranged from 5.80 cm (G. indica) to 27.65 cm (G. xanthochymus), while, fruit weight varied from 15.10 g (G. indica) to 172.00 g (G. xanthochymus); total soluble solids (TSS) in rind and pulp showed wide ranges (7.8–26.6 and 1.8–26.0 °Brix, respectively), with a notable negative correlation between fruit length and TSS. Principal component analysis (PCA) revealed that tree spread (PC1: 41.18%), leaf traits (PC2: 33.92%), and tree height/girth (PC3: 12.79%) were key discriminators, collectively explaining 87.89% of total variability. Cluster analysis segregated species into two groups namely, G. indica and G. mundro clustered together, while, G. xanthochymus formed a distinct group. Promising accessions were identified, including G. xanthochymus R2P4 with large fruit size (7.72 cm), weight (241.76 g), high TSS (15.26 °Brix), and G. indica KR4P9 with high TSS (20.11°Brix) and low acidity (0.29%). These findings highlight the potential for selecting elite genotypes for breeding programs and underscore the importance of conserving phenotypic diversity in Garcinia species.